Annual Plan 2005-06 Approved Outlay 2005-06 - Planning Commission (Planning Commission, 2005)
In continuation of working group discussions held in Planning Commission, sectoral outlays relating to the Plan of your State for 2005-06 are approved as indicated in the statement, taking into account subsequent changes in some items of Additional Central Assistance. Existing ACAs for urban infrastructure and slum development have been integrated into a comprehensive mission for urban renewal under which urban local bodies can access substantial Central assistance for specific projects for upgrading infrastructure and alleviating urban poverty. Resources will be made available to the State under the ACA for the urban renewal mission for projects which meet the eligibility criteria prescribed by the Ministry of Urban Development and the Ministry of Urban Employment & Poverty Alleviation. The broad entitlement of the State, within which projects can be developed, has been indicated in the scheme of financing. Corresponding outlays may be earmarked in the State's Plan for 2005-06.
Planning Commission, State Plan Division